2015
DOI: 10.1074/jbc.m114.612366
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analyses of the Interactions between Rab11 and Rab14 Small GTPases with Their Shared Effector Rab Coupling Protein (RCP)

Abstract: Background: Rab14 regulates endosomal trafficking; however, its binding to Rab11-FIP effectors is a source of conflicting data. Results: Rab14 interacts with the canonical Rab-binding domain of RCP, and both Rab14 and RCP function in neuritogenesis. Conclusion: Rab11-RCP complex formation may precede recruitment of RCP by Rab14. Significance: This study provides a conceptual framework for Rab14 and RCP in health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…5A). A Q70L Rab14 single point mutation yields a constitutively active protein, while the S25N mutation yields a dominant-negative protein (37)(38)(39). First, we examined the role of Rab14 in cell proliferation using our novel cell lines.…”
Section: Active Rab14 Is Involved In Exosomal Traffickingmentioning
confidence: 99%
“…5A). A Q70L Rab14 single point mutation yields a constitutively active protein, while the S25N mutation yields a dominant-negative protein (37)(38)(39). First, we examined the role of Rab14 in cell proliferation using our novel cell lines.…”
Section: Active Rab14 Is Involved In Exosomal Traffickingmentioning
confidence: 99%
“…We previously described a role for Rab11-family interacting protein 1C (FIP1C; also known as Rab coupling protein or RCP) and Rab14 in HIV-1 Env trafficking and particle incorporation (13). FIP1C forms a parallel homodimer capable of binding to two Rab molecules through its C-terminal Rab binding domain (RBD) (14,15). In HeLa cells, FIP1C is largely concentrated in a perinuclear structure representing the endosomal recycling compartment (ERC) (16,17).…”
mentioning
confidence: 99%
“…Casanova JE et al reported that interaction between Rab25 and Rab11A was associated with the apical recycling system of polarized Madin-Darby canine kidney cells [57]. Besides, the competition assay by Lall P et al revealed that Rab25 can out-compete Rab14 for binding to FIP2 in vitro [58]. Moreover, He H et al reported that Rab25 expression was upregulated in a case series of 11 hepatocellular carcinomas and a cholangiohepatoma along with dysregulated expression of a number of other Rab proteins including Rab1B, Rab4B, Rab10, Rab22A and Rab24聽[59].…”
Section: Discussionmentioning
confidence: 99%